Yangjing Shugan decoction targets the Sirt1/Nrf2 antioxidant pathway and gut microbiota-metabolite axis to protect against premature ovarian failure - Yang, Ling; Liu, Li; Liu, Junbo; Xu, Meng Ran; Ren, Jing; Li, Bo; Jiao, Lili; Wei, Yunyan; Wang, Jing; Guo, Yi (Frontiers in Pharmacology, 2026)
ObjectiveThis study aimed to assess the therapeutic potential of Yangjing Shugan decoction (YJSGD) in D-galactose (D-gal)-induced Premature Ovarian Failure (POF) mice and to elucidate its underlying mechanisms.MethodsThe main metabolites in YJSGD were characterized. A D-gal-induced POF mouse model was established and intervened with YJSGD at doses of 25, 50, and 100 mg/kg. A comprehensive analysis encompassing ovarian function, oxidative stress, inflammation, the Sirt1/Nrf2 pathway, gut microbiota, short-chain fatty acids (SCFAs), and serum metabolomics was conducted.ResultsThe results demonstrated that YJSGD effectively restored estrous cyclicity, normalized serum estradiol (E2), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) levels, and improved ovarian follicular development. YJSGD treatment also enhanced systemic antioxidant capacity and attenuated inflammation. Mechanistically, the therapeutic effects were associated with the upregulation of the Sirt1/Nrf2 signaling pathway in the ovary, as evidenced by increased protein expression of Sirt1, Nrf2, and HO-1, and suppressed Keap1. Furthermore, YJSGD ameliorated gut microbiota dysbiosis, promoted beneficial SCFAs production, and rectified serum metabolic disturbances involved in amino acid, lipid, and energy metabolism.ConclusionThe results indicate that YJSGD is a promising multi-target agent for POF treatment, and its synergistic effects on reproductive, oxidative, and gut microbiota homeostasis provide a solid basis for its clinical application.